Ionic Conductivity and Dielectric Properties of CMC Doped NH4SCN Solid Biopolymer Electrolytes - N.A.M. Noor,; M.I.N. Isa (Trans Tech Publications, 2024)
In this work, solid biopolymer electrolytes (SBE) containing carboxymethyl cellulose (CMC) doped with ammonium thiocyanate (NH4SCN) were prepared via solution casting method. The ionic conductivity and dielectric properties of CMC-NH4SCN system were investigated by electrical impedance spectroscopy in the temperature range of 303-353 K. The dc conductivity shows that the highest ionic conductivity of 6.48 x 10-5 Scm-1 at ambient temperature was obtained when 25 wt.% of NH4SCN was incorporated. The temperature dependence of ionic conductivity revealed that CMC-NH4SCN system was discovered to obey Arrhenius law where the regression value is almost unity (R2?1). Activation energy of CMC-NH4SCN system was found to decrease with the increment of NH4SCN concentration. The dielectric behaviour of the CMC-NH4SCN system have been analyzed using dielectric permittivity (?*) and electrical modulus (M*) spectra. Results from dielectric studies showed a non-Debye behaviour of CMC-NH4SCN system